2011
DOI: 10.3109/07420528.2010.549599
|View full text |Cite
|
Sign up to set email alerts
|

Morningness-Eveningness, Chronotypes and Health-Impairing Behaviors in Adolescents

Abstract: The impact of diurnal preferences on health-related behaviors is acknowledged but relatively understudied. The aim of this study was threefold: (1) testing the measurement model of the Hungarian version of the reduced Horne-Östberg Morningness-Eveningness Questionnaire (Hungarian Version of the rMEQ); (2) estimating chronotypes and their prevalence; and (3) analyzing the relationship between morningness-eveningness/chronotypes and health-impairing behaviors, including smoking, alcohol use, and physical inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
139
6
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(171 citation statements)
references
References 58 publications
18
139
6
8
Order By: Relevance
“…ET subjects reported higher consumption -sporadic and habitual-of the three substances. Subsequent international studies have confirmed this observation, and this is of special relevance for adolescent and adult 30 populations (Andershed, 2005;Gau et al, 2007;Urbán et al, 2011;Giannotti et al, 2002;Wittmann et al, 2006). Prat & Adan (2011) have also found ET subjects consumed more illegal drugs (cannabis, ecstasy and cocaine) and hazardous alcohol use than MT.…”
Section: Addictionsmentioning
confidence: 66%
“…ET subjects reported higher consumption -sporadic and habitual-of the three substances. Subsequent international studies have confirmed this observation, and this is of special relevance for adolescent and adult 30 populations (Andershed, 2005;Gau et al, 2007;Urbán et al, 2011;Giannotti et al, 2002;Wittmann et al, 2006). Prat & Adan (2011) have also found ET subjects consumed more illegal drugs (cannabis, ecstasy and cocaine) and hazardous alcohol use than MT.…”
Section: Addictionsmentioning
confidence: 66%
“…En esta línea, los fumadores presentan una marcada tendencia hacia la vespertinidad, así como grandes diferencias a la hora de levantarse de lunes a viernes respecto a los fines de semana (Randler, 2008b;Urbán et al, 2011). También en consumidores crónicos de alcohol es común la presencia de un aplanamiento de la amplitud rítmica tanto de la temperatura corporal como de la melatonina, situación que se vería potenciada por el síndrome de abstinencia (Adan, 2010).…”
Section: Consumo Abuso Y Dependencia De Sustanciasunclassified
“…rMEQ's validation studies (e.g., Jankowski, 2013;Randler, 2013;Urbán et. al., 2011), suggest one item (rMEQ-5) to consistently load strongly on its principal factor.…”
Section: Self-assessment Of Chronotypementioning
confidence: 99%